ANALISIS PENYERAPAN BUDAYA KUALITAS TERHADAP KEBERHASILAN PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001 DI PERUSAHAAN KAWASAN JABABEKA CIKARANG - Huda, Miftakul; ., Nurhidayati (2020)
The purpose of this research background to the problem in this study is based on the problems that have occurred including an increase in complaints from customers due to defective products from 2015 to 2019 and a decrease in the customer satisfaction index from 2018 to 2019. The purpose of this study is (1) to determine how much the level of quality culture absorption of employees in the company Jababeka Dua area. (2) To find out how big the level of application of the principles of ISO 9001 quality management systems in the Jababeka Dua area company. (3) Knowing the effect of the absorption of quality culture on the implementation of the ISO 9001 quality management system in the Jababeka Dua area company. The data of research were obtained from a sample of 125 respondents randomly selected employees and proportionate in each work unit. The Method of analisys used in testing the relationship between latent constructs the quality culture to the succesful implementation of quality management system ISO 9001 is Structural Equation Modeling (SEM) using AMOS V.24. This research found that the quality culture on employees and the implementation of quality management system ISO 9001 has been well perceived by employees. Based on full model analysis, the result of this research shows that full model fill goodness of fit. Overall construct indicators, that is philosophy, beliefs, habits, behavior, values, traditions, procedures, and expectations are valid and reliable in measuring the construct of quality culture, and top management commitment, supplier partnerships, continuous improvement, employees involvement, customer focus, and product quality are valid and reliable in measuring the construct of the implementation of quality management system iso 9001. hypothesis testing showed result consistent with the theoretical study that the quality culture positive and significant impact on the implementation of the quality management system ISO 9001.